Gold‐Catalyzed Atroposelective Synthesis of 1, 1′‐Binaphthalene‐2, 3′‐diols. (23rd January 2020) - Zhang, Jianwei; Simon, Martin; Golz, Christopher; Alcarazo, Manuel
Abstract: A highly atroposelective (up to 97 % ee ) Au‐catalyzed synthesis of 1, 1′‐binaphthalene‐2, 3′‐diols is reported starting from a range of substituted benzyl alkynones. Essential for the achievement of high enantioselectivity during the key assembly of the naphto‐3‐ol unit is the use of TADDOL‐derived α‐cationic phosphonites as ancillary ligands. Preliminary results demonstrate that the transformation of the obtained binaphthyls into axially chiral monodentate phosphines is possible without degradation of enantiopurity. Abstract : Ferngesteuert : Zwei Methylgruppen, die sich strategisch am Rückgrat der Imidazolium‐Komponente eines Katalysators auf Goldbasis befinden, sind unerlässlich, um die gewünschten Binaphtholverbindungen in bis zu 97 % ee zu liefern.